SCIENCE PROCESS SKILLS ANALYSIS OF CLASS IV STUDENTS OF KANISIUS SENGKAN YOGYAKARTA ELEMENTARY SCHOOL IN SCIENCE LEARNING CONTENT - Ginting, Barnabas; Limiansih, Kintan; Hadiyanti, Agnes Herlina Dwi (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2023)
This study aims to determine the level of proficiency in science process skills of fourth grade students at Kanisius Sengkan Elementary School, Yogyakarta. This type of research is descriptive quantitative. The subjects of this study were 4th grade students of Kanisius Sengkan Elementary School, Yogyakarta. The research method used is an investigative method using simple statistical analysis techniques. The population used was fourth grade students at Kanisius Sengkan Elementary School, Yogyakarta. The sample was obtained using voluntary sampling method, so that the sample obtained was 82 students. Data collection using a test engine with a total of 25 multiple choice questions. The results showed that the science process skills (SPS) of the 4th graders of Kanisius Sengkan Primary School Yogyakarta in terms of the content of scientific learning were very high, because the science process skills of each school were mostly high with an overall score of 66%. The science process skills (SPS) that are best mastered by students in each school are grouping, interpreting, predicting, using tools and materials, asking questions, and communicating. The science progress skills (SPS) of the 4th grade students of Kanisius Sengkan Primary School Yogyakarta in terms of learning science content are relatively high. However, some scientific process skills (competencies) have not been mastered optimally by students in each school, such as observation, planning experiments, conducting experiments and forming hypotheses.